Assessing Pharmacy Students’ Self-Perception of Cultural Competence - Echeverri, Margarita (2013)
Pharmacists play an increasingly important role in medication therapy management, which requires communicating effectively with patients. Pharmacy students completed the Self-Assessment of Perceived Level of Cultural Competence (SAPLCC) questionnaire, and their results were used to identify patterns in self-assessment of cultural competence. In general, students rated their knowledge as less than their skills and attitudes. Important differences were found by race, comparing each group with its counterparts: African American students rated their perceived competencies regarding patient discrimination and barriers to health care at a significantly higher level; Asian American students rated their attitudes to engaging in self-reflection and their knowledge in multicultural issues at significantly lower level; and White students rated their awareness regarding racial dynamics at a significantly lower level. It is recommended to consider the students’ cultural, racial, and ethnic backgrounds before developing curriculum in cultural competence and, perhaps, to develop targeted educational interventions for specific groups.